Cattle in the Flint Hills: The Texas – Kansas Connection - Jim Hoy (Symphony in the Flint Hills, 2010)
The cattle industry of the Flint Hills had its origin along the Rio Grande River nearly four centuries ago. Even today, as they did in my boyhood, many of the summer cattle that graze Flint Hills bluestem come from the brush country of south Texas, and some from below the Rio Grande in Old Mexico.
Keywords: cattle; Flint Hills; bluestem; graze; Texas; Old Mexico; Rio Grande; New Spain; livestock; cows; Comanche; Kiowa; Native Americans; Indians; Nueces; Great Plains; industry; beef; hides; Shawnee Trail; trade; Civil War; union; confederacy; Joseph McCoy; Abilene; Chisholm Trail; railroad; cowboy; rancher; herd; longhorn; Texas cattle; American cattle; Chase county; Butler county; Angus; Brahmas; Herefords; Grand Summit; Virgil; Cassoday; Matfield Green; Bazaar; Volland; stockyards